Legal and economic dilemmas of sustainable development in times of global crisis - Rudnicki, Maciej (Studia Ecologiae et Bioethicae, 2020)
The starting point for the reflections were a range of issues bordering philosophy, morality, economy and law, regarding the rational management of natural resources and protection of the natural environment, as well as the regulation and forming of peoples’ attitudes and behaviours in relation to the natural environment, and the setting of legal boundaries for those behaviours and sanctions for crossing them. The state of the natural environment has a very strong influence on the fulfilment of existential human needs. Humans strive for satisfactory life of appropriate quality, and often have to make choices between various goods. Unfortunately, ecological properties are very often treated last of all in the decision-making hierarchy, and are usually considered inferior to, for example, material prosperity or social comfort. Treating the ecological properties as such, often results in them going unnoticed overall, and very soon leads to permanent and negative changes that directly affect human life and the environment, as well as having a negative effect on health. Therefore, such extraordinarily essential conditions for choosing and fulfilling ecological needs as regards first-class existential needs that have a vital influence on the quality of life and ecological awareness, are based chiefly on understanding the rules of sustainable development. Should the development of civilisation be ruled by economy, or should the basis of that development be protection and maintenance of natural environmental resources? Or maybe the most sensible option is to balance economic, social and ecological aims? The problem pinpointed in this way highlights the importance in life of global community, and may for years induce consideration and reflection.